Pendekatan Teologis-Normatif dalam Pluralisme Beragama di Indonesia - 'Ulum, Iftah Bahrol; Mawardi, Kholid (Ikatan Da'i Indonesia, 2024)
This article aims to describe a normative theological approach to religious pluralism in Indonesia. The research method used is a literature study approach through library sources from various literature sources with a normative theological approach in religious pluralism. Then analyze and present the data findings objectively. The result of this research is the implementation of a normative approach in religious pluralism in Indonesia through two elements, namely; first, upholding religious tolerance by mutual respect and respect between religious communities in accordance with the practice of Pancasila. secondly, the attitude of mutual help in religion which is manifested in the form of mutual cooperation in helping others to realize the welfare of each other's lives. This means that religious pluralism is an important point in the life of society in Indonesia which has a diverse population of different races, ethnicities, ethnicities and religions.